DUALITY FOR A NONDIFFERENTIABLE MULTIOBJECTIVE HIGHER-ORDER SYMMETRIC FRACTIONAL PROGRAMMING PROBLEMS WITH CONE CONSTRAINTS - Dubey, R.; Gupta, S. K. (Journal of Nonlinear Analysis and Optimization: Theory & Applications (JNAO), 2016)
In this paper, a pair of nondifferentiable multiobjective higher-order symmetric fractional dual problem with cone constraints is formulated. For a differentiable function, we introduce the definition of higher-order (C,α,ρ,d)- convexity. Next, we prove appropriate duality relations under aforesaid assumptions.